Open aortic valvotomy for congenital aortic stenosis. Late results. Issue 1 (January 1982) - Presbitero, P; Somerville, J; Revel-Chion, R; Ross, D
Abstract : Forty-nine consecutive patients, aged 2 to 28 years, were followed after open aortic valvotomy. Three late deaths occurred in relation to reoperation. Seventeen reoperations were performed 2 to 14 years after valvotomy for severe stenosis in 12 patients, aortic regurgitation in three patients, and aortic stenosis and regurgitation in two patients. Among the 12 patients who required reoperation for severe obstruction, five aged over 19 years had calcified valves with normal aortic roots and valve replacement was simple. Seven had tunnel obstruction with a hypoplastic aortic root, constituting a difficult surgical problem, and necessitating total aortic root replacement in four. The postoperative course after simple aortic valvotomy is determined by several factors; the basic pathological form of the obstruction is the most important. Those who present in the first decade with lumpy valves and small aortic roots tend to form a diffuse tunnel obstruction when residual stenosis remains after valvotomy; older patients with pliable domed valves slowly develop calcified cusps and present less problems as the aortic root is usually a good size. Although aortic valvotomy offers good early results with a low mortality, it should be regarded as palliative as all patients will ultimately require reoperation. Younger patients with lumpy valves and a small aortic root have more problems and may require different initial management.